2013
DOI: 10.1097/ncc.0b013e31824062d1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Changes Among Breast Cancer Patients in Malaysia

Abstract: This will be helpful to dietitians in providing a better understanding of good eating habits that will maintain patients' health after breast cancer diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(74 citation statements)
references
References 16 publications
1
66
5
2
Order By: Relevance
“…These changes in food consumption resulted in decreased energy intake, as shown in previous studies,12, 20, 25, 26 but also in poorer micronutrient and fiber intakes. Only 3 studies quantified nutrient intake variations between before and after diagnosis 20, 22, 27.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…These changes in food consumption resulted in decreased energy intake, as shown in previous studies,12, 20, 25, 26 but also in poorer micronutrient and fiber intakes. Only 3 studies quantified nutrient intake variations between before and after diagnosis 20, 22, 27.…”
Section: Discussionsupporting
confidence: 74%
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations